Analysis of the VP2 protein gene of canine parvovirus strains from affected dogs in Japan - Soma, Takehisa; Taharaguchi, Satoshi; Ohinata, Tsuyoshi; Ishii, Hiroshi; Hara, Motonobu (Research in veterinary science, 2013)
To clarify the evolution of canine parvovirus 2 (CPV-2) that has recently been epidemic in Japan, VP2 gene sequences at positions 3556–4166 were analyzed in 107 CPV-2 strains obtained from rectal swabs of diarrheic dogs from 2009 to 2011. CPV-2b (95 strains) was more frequently detected than CPV-2a (nine strains), while CPV-2c was not detected. Remaining three strains were identified as the original type CPV-2, which should be derived from vaccines. These findings are similar to the previous results involving Japanese strains, suggesting there has been no great change in the recent CPV-2 epidemic in Japan. This epidemic is the same as that in Taiwan. Furthermore, a 324-lle mutant, which has been reported in Korean and Chinese strains, was detected in 66.7% of CPV-2a strains.